Problemy instytucjonalizacji etyki w dziedzinie służby zdrowia - Kubka, Janina; Vasiljeviene, Nijole (Annales. Etyka w Życiu Gospodarczym, 2008)
Life in good health and health security prove the most significant values highlighted by moral philosophy in the time of the environmental crisis. The imperfect operation of healthcare poses a threat for humans. Administrative measures regulate insufficiently medicine and healthcare. They need to be backed up by ethics, which cannot be seen solely as ethics of an individual’s conscience. What is needed is professional, practice-oriented and institutionalized-within-healthcare-organizations ethics. Recently, there have appeared a great number of new international documents setting standards of medical procedures in compliance with the requirements of the new bioethical values. At the same time elements of the ethical infrastructure such as bioethics commissions or committees have been created. In the face of the specificity and the complexity of ethical issues and problems encountered within contemporary medical practice the requirement of high ethical competence of all healthcare workers often fails to be sufficient.